Kebaya dan Berkebaya: Tinjauan Atas Gaya Berkebaya Perempuan dari Komunitas Kebaya di Jakarta - nita trismaya (Faculty of Arts and Design, Jakarta Institute of the Arts, 2024)
Abstract For the last few years, the women movement from kebaya community has been emerged with a mission to reappearing kebaya as national dress. The reason behind this is that kebaya has been detraditionalized since post reformation era in 1998 due to social, politic, and culture transformations in Indonesia. This retraditionalization movement is interpreted as a respond to detraditionalization of kebaya. Furthermore, this social symptom is raising questions; what happen to kebaya nowadays and how the women from kebaya community define kebaya as a result of retraditionalization? This article uses ethnographic research method, it includes fieldworks, participants observation, interviews and observations using social media. The research findings are analyzed by using anthropology theory of dress to understand more about kebaya and the women who wore it. The results of this research are expected to bring new perspectives about study of kebaya based on anthropology and design studies. Keywords : wearing kebaya, kebaya, kebaya community, women, retraditionalization Abstrak Beberapa tahun terakhir ini muncul gerakan perempuan dari komunitas kebaya yang berupaya mengembalikan kebaya sebagai busana nasional. Hal ini disebabkan kebaya telah mengalami detradisionalisasi pasca reformasi tahun 1998 akibat terjadinya perubahan sosial, politik dan budaya di Indonesia. Gerakan kembalinya kebaya ini dimaknai sebagai retradisionalisasi sebagai respon atas detradisionalisasi kebaya. Gejala sosial ini selanjutnya menimbulkan pertanyaan; apa yang terjadi dengan kebaya saat ini dan bagaimana para perempuan dari komunitas kebaya mendefinisikan kebaya hasil retradisionalisasi? Tulisan ini menggunakan metode penelitian etnografi yakni pengamatan di lapangan, observasi partisipasi, wawancara dan pengamatan melalui media sosial. Temuan penelitian dianalisa memakai teori antropologi pakaian untuk memahami kebaya dan para perempuan yang memakainya. Hasil penelitian ini diharapkan membawa kebaruan mengenai kajian kebaya ditinjau dari keilmuan antropologi dan desain. Kata Kunci: berkebaya, kebaya, komunitas kebaya, perempuan, retradisionalisasi